Genetic variation associated with childhood and adult stature and risk of MYCN‐amplified neuroblastoma. (17th September 2020) - Semmes, Eleanor C.; Shen, Erica; Cohen, Jennifer L.; Zhang, Chenan; Wei, Qingyi; Hurst, Jillian H.; Walsh, Kyle M.
Abstract: Background: Neuroblastoma is the most common pediatric solid tumor. MYCN ‐amplification is an important negative prognostic indicator and inherited genetic contributions to risk are incompletely understood. Genetic determinants of stature increase risk of several adult and childhood cancers, but have not been studied in neuroblastoma despite elevated neuroblastoma incidence in children with congenital overgrowth syndromes. Methods: We investigated the association between genetic determinants of height and neuroblastoma risk in 1538 neuroblastoma cases, stratified by MYCN ‐amplification status, and compared to 3390 European‐ancestry controls using polygenic scores for birth length (five variants), childhood height (six variants), and adult height (413 variants). We further examined the UK Biobank to evaluate the association of known neuroblastoma risk loci and stature. Results: An increase in the polygenic score for childhood stature, corresponding to a ~0.5 cm increase in pre‐pubertal height, was associated with greater risk of MYCN ‐amplified neuroblastoma (OR = 1.14, P  = .047). An increase in the polygenic score for adult stature, corresponding to a ~1.7 cm increase in adult height attainment, was associated with decreased risk of MYCN ‐amplified neuroblastoma (OR = 0.87, P  = .047). These associations persisted in case‐case analyses comparing MYCN ‐amplified to MYCN ‐unamplified neuroblastoma. No polygenic height scores were associated with MYCN ‐unamplified neuroblastoma risk. Previously identified genome‐wide association study hits for neuroblastoma (N = 10) were significantly enriched for association with both childhood ( P  = 4.0 × 10 −3 ) and adult height ( P  = 8.9 × 10 −3 ) in >250 000 UK Biobank study participants. Conclusions: Genetic propensity to taller childhood height and shorter adult height were associated with MYCN ‐amplified neuroblastoma risk, suggesting that biological pathways affecting growth trajectories and pubertal timing may contribute to MYCN ‐amplified neuroblastoma etiology. Abstract : We investigated the association between genetic determinants of height and neuroblastoma risk in 1538 neuroblastoma cases, stratified by MYCN ‐amplification status, and compared to 3390 European‐ancestry controls using polygenic scores for birth length, childhood height, and adult height. Genetic propensity to taller childhood height and shorter adult height were associated with MYCN ‐amplified neuroblastoma risk, suggesting that biological pathways affecting growth trajectories and pubertal timing may contribute to MYCN ‐amplified neuroblastoma etiology. Graphical abstract created with BioRender.com and height icon by Becris from the Noun Project.